Fostering linkages between transnational corporations and small to medium-sized enterprises in Brazil - Botelho,Delane (2011)
When large Transnational Corporations (TNCs) enter a host country, consequent development of local Small and Medium Enterprises (SMEs) is expected. The public sector may play an important role by fostering Business Linkages (BL), by which TNCs establish purchasing relationships with local SMEs. This article was motivated by growing attention in literature to the interaction between economic development and the ability of companies to absorb and disseminate competences. Its purpose is to understand the role of public policy programs that promote BLs for development by: (a) analyzing actions and programs developed by public and private institutions to foster BL in Brazil; (b) discovering the participants' benefits from such actions and programs; and (c) identifying opportunities for public sector promotion of BL. The research design was a multiple case study which analyzed Supplier Development Projects in five Brazilian states. Results indicate that public policies may complement overall development as well as industrial policy, which is related to capacity building, stimulating technology transfer, and, more broadly, promoting a business friendly environment able to attract investment for development, calling for a regional and sub-regional approach for a country the size of Brazil.